Three-dimensional angularity characterization of coarse aggregates based on experimental comparison of selected methods. (2nd January 2022) - Fang, Huaiying; Zhu, Hejun; Yang, Jianhong; Huang, Xiaoyu; Hu, Xiang
Abstract: The angularity of the coarse aggregate (CA) affects the performance of the concrete. A digital microscope is used to obtain three-dimensional contour data points on the surface of a CA and thus improve the effectiveness of the evaluation of the angularity of the CA. Three methods of characterizing the angularity of the CA, namely applying a fitted ellipsoid model ( AIf ), steradian model ( AIc ), or roughness model ( SR ), were studied. The effectiveness of different angularity characterization methods was compared with the Los Angeles abrasion (LAA) and void content (VC) experiments. Results show that the angularity index of the fitted ellipsoid model is the most effective model in characterizing aggregate angularity, and it can eliminate the influence of the particle sizes; the angularity index AIf changes most rapidly with an increase in the VC, indicating that AIf is the most effective in characterizing the VC of the CA; and the angularity index AIc has a strong negative correlation with sphericity, which indicates that AIc is the most effective index in characterizing the sphericity of the CA. Highlights: A new algorithm (fitted ellipsoid model) for evaluating the 3D angularity of aggregates has significant advantages. The angularity index AIf is more suitable for characterizing the void content of the aggregate. The angularity index AIc is more suitable for characterizing the sphericity of the aggregate.